Financial Distress in Indonesia's Transportation and Logistics Sector: The Role of Firm Size, Financial Performance and Corporate Governance - Farida Titik Kristanti; Christina Azaliah (Academic Bright Collaboration, 2026)
Purpose – This study investigates the influence of firm size, leverage, liquidity, board size, and women on board on financial distress in transportation and logistics companies listed on the Indonesia Stock Exchange (IDX) during 2020-2024. The sector's exposure to high debt burdens, operational costs, and post-pandemic economic uncertainty makes understanding the drivers of financial distress critical for corporate governance and financial risk management Methods – A quantitative approach was applied using secondary data from annual reports sourced from the IDX and company websites. Purposive sampling produced 27 companies over five years (135 observations); after removing grey-area classifications, 121 observations were retained. Financial distress was measured using the Altman Z-Score, converted into a binary outcome. Findings – The Omnibus Test confirms that all five variables jointly and significantly predict financial distress (χ² = 15.399, df = 5, p = 0.009). Partially, firm size (β = 0.091, p = 0.387), leverage (β = 0.007, p = 0.735), liquidity (β = -0.026, p = 0.486), and board size (β = 0.240, p = 0.150) show no significant individual effects. Women on board is the only variable with a significant negative effect (β = -1.654, p = 0.001), indicating that female board representation substantially reduces the probability of financial distress. Research implications – The findings are confined to a single industry sector on the IDX, limiting cross-sector generalizability. The binary classification of financial distress via the Altman Z-Score may obscure intermediate financial conditions. Future studies are encouraged to explore additional governance variables, extend the time horizon, and apply alternative distress prediction models across broader industry contexts. Originality – This study uniquely combines financial performance and board gender diversity indicators to predict financial distress within Indonesia's transportation and logistics sector, an underexplored context in the existing literature. The focus on the post-pandemic period (2020-2024) and the significant role of women on board offer new empirical insights for both scholars and practitioners on gender-inclusive governance as a financial risk mitigator.